Trapped! - A Framed Novel - James Ponti (Bharat Simon & Schuster, 2018)
Florian Bates$1 (Bthe only kid on the FBI Director$1 (Bs speed dial and several international criminals$1 (Bmost wanted lists$1 (Bmust save his friend from being framed for a crime he didn$1 (Bt commit in this hilarious third novel in the Framed! series.s
Keywords: Mystery -- Mystery